Sex-specific associations of serum cotinine levels with depressive symptoms and sleep disorders in American adults: NHANES 2007-2014 - Yang, Hongguang; Liu, Yao; Huang, Zhenhe; Deng, Guifang (Frontiers in Psychiatry, 2024)
BackgroundAccumulating evidence have demonstrated that tobacco smoke exposure (TSE) causes damage to human mental issues. However, previous studies almost focus on the individual smoking exposure patterns and some inconsistent results are reported. Serum cotinine is a reliable and quantitative biomarker of TSE. This study aims to explore the association of serum cotinine with depression and sleep disorders and the potential gender differences.MethodsData from the National Health and Nutrition Examination Survey (NHANES) 2007-2014 was used. Weighted multiple logistic regression methods, generalized additive models (GAM), and restricted cubic spline (RCS) models were used for association analyses. Moreover, gender-stratified analyses were conducted.ResultsOf 12,599 individuals included in the final analysis, 1,295 had depression, 3245 had trouble sleeping and 1152 had diagnostic sleep disorders. After adjusting for potential covariates, linear relationship suggested higher serum cotinine levels were positively associated with risk of depression and sleep disorders, including self-reported trouble sleeping and diagnostic sleep disorders in the total sample and female participants, and serum cotinine levels were positively correlated with depression and trouble sleeping in male participants. Additionally, inverted L-shaped associations between serum cotinine and depression and sleep disorders were detected, and at the same cotinine level, females have a higher risk of experiencing depression and sleep disorders.ConclusionsIn this study, higher serum cotinine increased the risk of depression and sleep disorders and there was stronger association in females than males. These findings provided novel evidence about how TSE affected the mental condition of the general US population.